THE EFFECT OF COLORING PICTURES ON FINE MOTOR DEVELOPMENT OF PRESCHOOL CHILDREN 4-6 YEARS OLD AT KINDERGARTEN DHARMA WANITA I WERUNGOTOK NGANJUK - Budi Utami, Rahayu; Dwiyanti, Adelia Nur (SYNTHESIS Global Health Journal, 2024)
Background. Stimulation of preschool children's fine motor skills needs to be done as a start to writing and drawing. Improving fine motor skills requires stimulation, one of which is to improve the fine motor skills of coloring pictures. Coloring pictures has many benefits, namely as a medium for color recognition, stimulating the sense of sight, and helping to solve problems. This study aims to determine the effect of coloring pictures on the fine motor development of preschool children aged 4-6 years at Dharma Wanita I Werungotok Nganjuk Kindergarten. Research Method. This study used a pre-experimental approach with a one-group pre-post-test design. The study population was pre-school children aged 4-6 years as many as 29 children. The sampling technique used was total sampling. Statistical tests used the Wilcoxon Test with ?? 0.05. Findings. The results showed that of the 29 respondents, the fine motor development of children before coloring pictures was almost half, namely 11 respondents (37.9%) had dubious fine motor development. After the coloring picture was done, most of the 22 respondents (75.9%) had fine motor development according to development. The Wilcoxon test results obtained p value = 0.000 ? ? = 0.05 so that Ha is accepted, meaning that there is an effect of coloring pictures on fine motor development in preschool children aged 4-6 years. Conclusion. Stimulation of coloring pictures is expected to be well implemented so that fine motor development in preschool children can improve in accordance with their age development.